Visual Experimental Study of Influence of Fuel Rod Bundle Spacing on Fission Gas Release under Fuel Cladding Failure Conditions - LI Shengkang, CAI Jiejin (Yuanzineng kexue jishu)
The release of fission gases from damaged cladding of pressurized water reactor fuel rods can significantly affect the flow and heat transfer characteristics in sub-channel. The presence of these escaping bubbles can lead to increase of localized temperature in the sub-channel, while high-velocity bubbles may cause deformation of the fuel rods, thereby impacting the safe operation of the nuclear reactor. Current research primarily focuses on fluid flow patterns, neglecting the influence of rod bundle spacing on bubble behavior within the sub-channel. To investigate the effect of fuel rod spacing on the behavior of escaping bubbles, this study employs refractive index matching techniques to eliminate optical errors caused by the rod bundles and utilizes high-speed photography to visualize the escaping bubbles rising at different rod bundle spacings. A 3×3 rod bundle arrangement was adopted with five sets of rod bundle spacings (d=12.6, 14.6, 16.6, 18.6, 20.6 mm). The results show that stable bubbles exhibit a zigzag ascent trajectory, which can be quantitatively represented using trigonometric functions. The mean squared error (MSE) of the fitting function for the rising trajectory increases with the rod bundle spacing. At a spacing of d=14.6 mm, the right-side escaping bubbles have the highest angular wave number and the lowest horizontal amplitude. As the rod bundle spacing d increases, the average horizontal displacement of the right-side escaping bubbles increases while the angular wave number decreases. Conversely, the front-side escaping bubbles do not follow this trend and tend to rise almost vertically. The velocity of escaping bubbles within the range of rod spacing d=14.6-16.6 mm increases significantly, ranging from 4.90% to 7.48%. This not only ensures the compactness of the fuel assembly, but also releases fission gases more quickly, improving the efficiency of safe operation of pressurized water reactors. Escaping bubbles maintain an elliptical shape during rising, with an aspect ratio consistently less than 1. The front-side escaping bubbles are flatter than those on the right side. The right-side escaping bubbles have an average aspect ratio of approximately 0.66-0.85, an average We of about 0.12-0.23, and an average Eo of around 14-20. The front-side escaping bubbles have an average aspect ratio of approximately 0.59-0.88, an average We of about 0.10-0.22, and an average Eo of around 13-26. The variation in bubble tilt angle was positively correlated with the change in horizontal displacement. As the horizontal displacement increases, the tilt angle also increases. Traditional drag prediction models have not effectively predicted the drag coefficient under the experimental conditions of this study. Therefore, this paper proposes a drag prediction equation based on the ratio of rod bundle spacing to the equivalent diameter of the bubbles, as well as the inertial and surface tension forces that are valid for all experimental conditions. Validation shows that the discrepancies between the predicted and experimental values are all less than 20%.